Ensino superior em saúde através de atividades de extensão universitária durante a pandemia de Covid-19: a telereabilitação de paciente idoso como estratégia de formação do fisioterapeuta - CONCEIÇÃO, Ana Beatriz Souza da (2023)
The aging population requires that physical therapy students have adequate knowledge about caring for older adults. To this end, universities have included extension activities in their curricula, dedicated to providing physical therapy interventions for older adults. However, social isolation during the pandemic of COVID-19, induced the undergraduate program to replace their presential teaching activities with digital modes. In this context, telerehabilitation became the alternative for maintaining physical therapy intervention for older patients in social isolation and for maintaining academic activities. The aim of this study is to report the experiences of three Physical Therapy students during the tele-rehabilitation of an elderly couple and, at the same time, to analyze the effectiveness of the teaching strategy for the training of physical therapy professionals. The phases of the course proposed by the university professors were reported, which included assessment and telerehabilitation, as well as discussion of clinical cases with the other students. Overall, the patients showed clinical improvements and the skills and knowledge proposed during the semester were fully and partially achieved. We conclude that telerehabilitation as an option for curricular practice activities provided an effective way to address the learning gaps caused by the pandemic.